Characterisation of superficial breakage using multi-size pilot mills. (1st October 2015) - Yahyaei, M.; Weerasekara, N.S.; Powell, M.S.
Graphical abstract: Highlights: A new approach is proposed to characterise superficial breakage of ore. A new superficial breakage rate is presented. The superficial breakage is dependent on the inter-particle stressing conditions. Abstract: Low energy surface breakage has a high frequency of occurrence and thus plays a significant role in grinding processes. Yet this superficial breakage is poorly understood, measured and modelled – forming the focus of this work. Pilot mills of 0.8–1.8 m diameter, designed to provide a predominantly surface breakage environment with efficient removal of the resultant progeny, are utilised to characterise superficial breakage. A new rate, that of superficial breakage (1/(kW h/m 2 )), is introduced which measures fractional superficial breakage rate per energy provided to the surface of the material. This methodology is proposed as being suitable for understanding and characterising the surface breakage behaviour of ores. Tests were conducted on two ores with different hardness. Superficial breakage rates varied from 2 to 16 (1/(kW h/m 2 )) for the different ores and mill sizes, indicating a good sensitivity to ore type and the need to understand the applied stress – related to mill size. The results show that a single 'surface breakage rate for use in mill modelling is incorrect as the rate of superficial breakage is dependent on the size of the mill and therefore the inter-particle stressing conditions.